2021
DOI: 10.1155/2021/6283076
|View full text |Cite
|
Sign up to set email alerts
|

Development of Acute Inflammatory Demyelinating Polyneuropathy 11 Days after Spinal Surgery: A Case Report and Literature Review

Abstract: Guillain–Barré syndrome (GBS) usually has a good prognosis; however, patients may develop sequelae without prompt treatment. We herein describe an 81-year-old woman who developed acute-onset excruciating thigh pain and weakness in her lower extremities after spinal surgery. We diagnosed acute inflammatory demyelinating polyradiculoneuropathy by a nerve conduction study, which showed findings of demyelination without cerebrospinal fluid analysis because of a spinal prosthesis. Although anti-GM1 and anti-GalNAc-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Timely recognition of neurological symptoms, coupled with neurophysiological evaluations and CSF analysis, is imperative for accurate diagnosis [8]. A literature review of 18 cases conducted by Kakehi et al revealed that unexplained atypical symptomps and abnormal NCS findings are useful for diagnosing GBS when CSF examination cannot be performed after spinal surgery [5]. In our case, NCS demonstrated a multifocal demyelinating process and CSF exhibited elevated protein levels.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Timely recognition of neurological symptoms, coupled with neurophysiological evaluations and CSF analysis, is imperative for accurate diagnosis [8]. A literature review of 18 cases conducted by Kakehi et al revealed that unexplained atypical symptomps and abnormal NCS findings are useful for diagnosing GBS when CSF examination cannot be performed after spinal surgery [5]. In our case, NCS demonstrated a multifocal demyelinating process and CSF exhibited elevated protein levels.…”
Section: Discussionmentioning
confidence: 63%
“…The administration of general or locoregional anesthesia preceding surgery may influence the natural course of GBS [4]. Notably, certain surgeries, particularly cardiothoracic, spine, and abdominal surgeries, have been associated with AIDP development [5][6][7]. Surgery may weaken the immune system, increasing susceptibility to infections and potentially triggering GBS through mechanisms such as autoimmunity or molecular mimicry [2,8].…”
Section: Introductionmentioning
confidence: 99%